Diagnostics, Treatment, and Follow-Up in Craniopharyngioma - Müller, Hermann L. (Frontiers in Endocrinology, 2011)
Craniopharyngiomas (CP) are partly cystic embryogenic malformations of the sellar and parasellar region. With an overall incidence of 0.5 to 2.0 new cases / million population / year, approximately 30 to 50% of all cases represent childhood CP. Typical manifestations at diagnosis are headache, visual impairment, polyuria/polydypsia, growth retardation, and significant weight gain. Therapy of choice in patients with favorable tumor localization is complete resection with the intention to maintain optical nerve and hypothalamic-pituitary functions. In patients with unfavorable tumor localization (hypothalamic involvement), a limited resection followed by local irradiation is recommended. The overall survival rates are high (92%). Recurrences after complete resection and progressions of residual tumor after incomplete resection are frequent post-surgical events. Accordingly, the appropriate time point of irradiation after incomplete resection is currently under investigation in a randomized multinational trial (KRANIOPHARYNGEOM 2007). Quality of life is substantially reduced in approximately 50% of long-term survivors due to sequelae, notably morbid hypothalamic obesity. Both, childhood CP and adult onset CP should be recognized as chronic diseases requiring constant monitoring of the consequences and appropriate medical resources for treatment in order to provide optimal quality of survival for patients.